2021
DOI: 10.1093/bjs/znaa009
|View full text |Cite
|
Sign up to set email alerts
|

Rectal cancer lateral lymph nodes: multicentre study of the impact of obturator and internal iliac nodes on oncological outcomes

Abstract: Background In patients with rectal cancer, enlarged lateral lymph nodes (LLNs) result in increased lateral local recurrence (LLR) and lower cancer-specific survival (CSS) rates, which can be improved with (chemo)radiotherapy ((C)RT) and LLN dissection (LLND). This study investigated whether different LLN locations affect oncological outcomes. Methods Patients with low cT3–4 rectal cancer without synchronous distant metastases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 21 publications
1
61
0
2
Order By: Relevance
“…However, the response rate in the nCRT-boost subgroup was 72.9%, meaning that more patients would avoid LLND. Especially, in line with the studies from the Lateral Node Study Consortium, patients with obturator nodes metastasis achieved a much higher response rate and a lower recurrence rate than those with internal iliac nodes metastasis (30). Significantly, compared with the nCRT subgroup, the rates of enteritis and dermatitis in the nCRT-boost subgroup were similar.…”
Section: A B D Csupporting
confidence: 75%
“…However, the response rate in the nCRT-boost subgroup was 72.9%, meaning that more patients would avoid LLND. Especially, in line with the studies from the Lateral Node Study Consortium, patients with obturator nodes metastasis achieved a much higher response rate and a lower recurrence rate than those with internal iliac nodes metastasis (30). Significantly, compared with the nCRT subgroup, the rates of enteritis and dermatitis in the nCRT-boost subgroup were similar.…”
Section: A B D Csupporting
confidence: 75%
“…Unlike mesorectal lymph nodes where size is just one of many factors associated with its malignancy, 39,41 LLR risks have been significantly associated with the size (SA) of an LLN 11,26,42,43 . Primarily enlarged LLNs (>10 mm) have LLR rates reaching 40% 16–18 and increase even further when remaining persistently enlarged after neoadjuvant treatment 8–10,26,43,44 . Ogura et al 9 found in a retrospective, international cohort of 1216 patients with re‐evaluation of all MRIs, that patients with LLNs measuring ≥7 mm on the primary MRI resulted in an LLR rate of 19.5% after 5 y.…”
Section: Lateral Lymph Nodes: Sizementioning
confidence: 99%
“…The evidence currently available demonstrates clinical implications related to the size and/or anatomical location of an LLN 8–13 . Sufficient awareness of LLNs and knowledge of their consequences is therefore necessary.…”
Section: Towards International Collaborationmentioning
confidence: 99%
See 2 more Smart Citations